Consumers Perception and Responsiveness to Bulk SMS Advertising in the Sudan - Mansour, Ilham H (Gezira Journal of Economic and Social Sciences, 2012)
Mobile advertising has emerged as one of the most popular applications in mobile commerce, particularly in the form of SMS (Short Message System) advertising. This study aimed to explore how people of Sudan, perceive and respond to SMS marketing. The study employed descriptive approach to analyze the responses of a cross-sectional survey carried out with 240 mobile-phone users in Khartoum State. The results of the survey indicate that consumers generally feel positively about receiving SMS advertising but they have some concerns about providing their personal data to advertising companies. These findings confirm previous literature on privacy issues surrounding mobile advertising where consumers have a strong fear of spam and misuse of their personal data. The findings also suggest that consumers expect advertising messages to be relevant, less frequent and incentive based.  The results also show high potential of SMS advertising in respect of level of advertising awareness and readership. Moreover, the results of the study indicate that there are many issues relating to this area, need to be addressed through future research.